1993
DOI: 10.1007/bf00015065
|View full text |Cite
|
Sign up to set email alerts
|

Light-independent synthesis of LHC IIb polypeptides and assembly of the major pigmented complexes during the initial stages of Pinus palustris seedling development

Abstract: Pinus palustris has a greatly reduced need for light to initiate chloroplast development in comparison to angiosperms. Light is not required for chlorophyll synthesis in dark-grown Pinus palustris seedlings. However, embryos do not contain chlorophyll, and synthesis is limited to seedlings having cotyledon lengths between about 0.5 cm and 2.0 cm. The final amount of chlorophyll accumulated by dark-grown seedlings is about one fifth of that in light-grown seedlingsat the same stage. The major light-harvesting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The P. palustris Lhcb sequences were also closely related to G. biloba type 1 and type 2 Lhcb sequences, showing between 85 and 97% identity at the amino acid level (Chinn and Silverthorne, 1993;Chinn et al, 1995). Since a previous study of LHCIIb accumulation in P. palustris indicated that the major polypeptides were expressed in the absence of light (Canovas et al, 1993), sequence-specific probes were constructed to determine whether individual Lhcb mRNAs are also expressed in the absence of light. The 3' UT sequences of each clone (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The P. palustris Lhcb sequences were also closely related to G. biloba type 1 and type 2 Lhcb sequences, showing between 85 and 97% identity at the amino acid level (Chinn and Silverthorne, 1993;Chinn et al, 1995). Since a previous study of LHCIIb accumulation in P. palustris indicated that the major polypeptides were expressed in the absence of light (Canovas et al, 1993), sequence-specific probes were constructed to determine whether individual Lhcb mRNAs are also expressed in the absence of light. The 3' UT sequences of each clone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neither sequence was expressed in embryos allowed to imbibe either in darkness or in light. However, both sequences were already expressed in 0.5-cm cotyledons that had initiated chlorophyll synthesis and chloroplast development (Canovas et al, 1993). The expression levels of both sequences increased during development and were approximately 2-fold higher in the light than in darkness.…”
Section: Light-regulated Expression Of Lhcbl *Pp1 and Lhcb2*pp2 Mrnasmentioning
confidence: 95%
See 3 more Smart Citations